In Silico Analysis of rbcl Protein and D-Ribulose 1,5-bisphosphate Bond - Ihwan, Ihwan; Sari, Dewi Ratih Tirto; Hakim, Luchman; Retnaningdyah, Catur; Arumingtyas, Estri Laras (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
The aim of this study was to determine the bond between the protein rbcL and D-Ribulose 1,5-bisphosphate by insilico. DNA sequences of the Mangrove Rhizophora mucronate rbcL gene DNA sequences from 7 different sources were obtained from NCBI for further alignment analysis using BioEdit software, phylogeny analysis using Mega6 software, molecular docking using PyRx software, preparation and visualization of docking results using Biovia Discovery Studio Visualizer software and analysis of the protein model quality based on the number of amino acid residues (Ramachandran plot analysis). The results of the docking molecular analysis showed interaction of 9 hydrogen bonds namely Asp203, Thr173, His294, Glu204, His327, Ser379, His298, Arg295, and Asn123 and 2 unfavorable bonds namely Lys177 and Lys175. This ligand and protein interaction complex was of good quality because the presence of amino acid residues in the most favored regions was greater than the amino acid residues in the disallowed regions outcomes